2020
DOI: 10.1029/2019jb018675
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Sources of the 2018 Palu, Indonesia, Tsunami Using Videos From Social Media

Abstract: The 2018 Palu tsunami contributed significantly to the devastation caused by the associated MW 7.5 earthquake. This began a debate about how the moderate size earthquake triggered such a large tsunami within Palu Bay, with runups of more than 10 m. The possibility of a large component of vertical coseismic deformation and submarine landslides have been considered as potential explanations. However, scarce instrumental data have made it difficult to resolve the potential contributions from either type of sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 43 publications
2
45
3
Order By: Relevance
“…All three sources, however, significantly underpredict runups observed in the southern part of the bay (south of ∼ − 0.75 + N), with a maximum of 5 m whereas observed runups reached up to 10.5 m. In contrast, runups are relatively well predicted in the northern part of the Bay by Jamelot et al (2019)'s and Ulrich et al (2019)'s coseismic sources, with a slight advantage for the latter. This agrees with conclusions of earlier studies that coseismic sources alone cannot explain the tsunami coastal impact, particularly in the south (e.g., Nakata et al, 2020;Sepúlveda et al, 2020). Consistent with these results, Figure 4 shows that measured or inferred time series of surface elevation are not well reproduced, particularly in the southern part of the bay.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…All three sources, however, significantly underpredict runups observed in the southern part of the bay (south of ∼ − 0.75 + N), with a maximum of 5 m whereas observed runups reached up to 10.5 m. In contrast, runups are relatively well predicted in the northern part of the Bay by Jamelot et al (2019)'s and Ulrich et al (2019)'s coseismic sources, with a slight advantage for the latter. This agrees with conclusions of earlier studies that coseismic sources alone cannot explain the tsunami coastal impact, particularly in the south (e.g., Nakata et al, 2020;Sepúlveda et al, 2020). Consistent with these results, Figure 4 shows that measured or inferred time series of surface elevation are not well reproduced, particularly in the southern part of the bay.…”
Section: Resultssupporting
confidence: 90%
“…shorter period waves generated by the coastal landslide were followed by longer period waves from the earthquake. Pakoksung et al (2019), Nakata et al (2020), and Sepúlveda et al (2020) identified and modeled landslides as the most important, if not the principal, contributors to the tsunami. Their landslide parameters and corresponding wave generation, however, were hypothetical and selected to match observations.…”
Section: Figure 1 | (A)mentioning
confidence: 99%
See 3 more Smart Citations